The Effect of E-Filing Implementation, Level of Understanding of Taxation, and Tax Sanctions on Individual Taxpayer Compliance in Submitting Annual Tax Returns - Sutopo, Ika Destiana Risti; Supriatiningsih, Supriatiningsih (Indonesian Journal of Advanced Research, 2025)
This study investigates the effects of E-Filing implementation, tax understanding, and tax sanctions on individual taxpayers’ compliance with annual tax return submission. Using a quantitative survey approach, data were collected from 300 respondents. Analysis was conducted with SmartPLS version 4, employing inner and outer models, alongside bootstrapping for hypothesis testing. Results indicate that E-Filing adoption, enhanced tax literacy, and enforcement of tax sanctions significantly improve taxpayer compliance. These findings underscore the importance of these factors in increasing compliance levels. The study offers valuable insights for tax authorities aiming to boost state revenue by reducing tax evasion and improving tax administration efficiency, ultimately contributing to optimized national revenue collection.